2012
DOI: 10.3102/0002831211419949
|View full text |Cite
|
Sign up to set email alerts
|

Are Principal Background and School Processes Related to Teacher Job Satisfaction? A Multilevel Study Using Schools and Staffing Survey 2003-04

Abstract: Using nationally representative samples for public school teachers and principals, the authors inquired into whether principal background and school processes are related to teacher job satisfaction. Employing hierarchical linear modeling (HLM), the authors were able to control for background characteristics at both the teacher and school levels. They found that 17% of the total variance in teacher job satisfaction is between schools, a statistically significant amount that indicates schools can make a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
140
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 46 publications
8
140
2
8
Order By: Relevance
“…Contrary to the findings of previous studies (Shen et al, 2012;Skaalvik & Skaalvik, 2009), slightly higher job satisfaction is observed among teachers in larger schools. This finding suggests that deeper analysis of this variable is required to examine its behaviour when controlling for other factors and to explore its interactions with other variables.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Contrary to the findings of previous studies (Shen et al, 2012;Skaalvik & Skaalvik, 2009), slightly higher job satisfaction is observed among teachers in larger schools. This finding suggests that deeper analysis of this variable is required to examine its behaviour when controlling for other factors and to explore its interactions with other variables.…”
Section: Discussioncontrasting
confidence: 57%
“…In general, higher levels of teacher satisfaction are found at smaller schools that lack problems of resources (Shen, Leslie, Spybrook, & Ma, 2012;Skaalvik & Skaalvik, 2009) or, for example, in schools that serve a low percentage of students from socioeconomically disadvantaged homes. Teachers at schools with students of lower socioeconomic status show lower rates of satisfaction (Matsuoka, 2015) and a greater predisposition to transferring to schools that serve families with higher socioeconomic status (Hanushek, Kain, & Rivkin, 2004).…”
Section: Teacher Satisfaction and Associated Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Las investigaciones más recientes abordan el estudio de la satisfacción laboral de los docentes desde una perspectiva holística identificando el efecto generado por las variables demográficas, personales del docente y del contexto escolar (Hanushek & Rivkin, 2007;Kyriacou, 2001;Sebastián, Allensworth & Huang, 2016;Shen et al, 2012;Skaalvik & Skaalvik, 2009;Spillane & Lee, 2013). Entre sus resultados, todas ellas coinciden en destacar el rol del director (liderazgo escolar como lo denominan organismos como la OCDE o la UNESCO) y el clima de la escuela como factores que impactan en el grado de satisfacción laboral de los docentes (Hanushek & Rivkin, 2007).…”
Section: El Papel De La Dirección Escolarunclassified
“…Aunque otros trabajos han apuntado similares hallazgos, todos ellos se refieren al ámbito internacional (Shen et al, 2012), o aportan datos a escala nacional como es el caso del estudio de Ramírez y D'Aubeterre (2007) en Venezuela. Nuestro estudio subraya el papel fundamental que la escuela tiene para mejorar la satisfacción laboral de los docentes, mejorando el clima escolar.…”
Section: La Dirección Escolar O El Clima De La Escuela: ¿Qué Es Más Iunclassified